Effect of annealing parameters on microstructure and mechanical property of hot-rolled 100Cr6 bearing ring. Issue 11 (23rd July 2016) - Qian, D.S.; Wang, K.W.; Liu, Q.L.; Hua, L.
Abstract : Isothermal spheroidising annealing treatment is a vital step for hot-rolled 100Cr6 bearing ring to transform the lamellar pearlite into granular pearlite, which can improve the structure and cutability of the bearing ring. In this study, the effect of spheroidising annealing parameters on the microstructure of a hot-rolled 100Cr6 bearing ring was studied. The results show that annealing temperature and holding time have a great effect on the size and roundness of carbide particles, while the annealing cooling rate just has a significant effect on the carbide particles' size. A series of mechanical tests indicate that all annealing parameters have a great influence on the tensile strength, plasticity and hardness, but make no difference on the elasticity. Considering the machinability and working performance, the rational annealing temperature, holding time and rapid cooling rate should be chosen. This paper is part of a Themed Issue on Recent developments in bearing steels.